Предмет: Математика,
автор: D0br9k
Вычислите, предварительно упростив числовое выражение с помощью формул сокращённого умножения
53^2 + 2*53*47 + 47^2/ 76^2 - 2*76*51 + 51^2
Помогите решить)
Ответы
Автор ответа:
0
(53^2 + 2*53*47 + 47^2) / (76^2 - 2*76*51 + 51^2) =
= (53 + 47)^2 / (76 - 51)^2 = 100^2 / 25^2 = (100 / 25)^2 = 4^2 = 16
= (53 + 47)^2 / (76 - 51)^2 = 100^2 / 25^2 = (100 / 25)^2 = 4^2 = 16
Автор ответа:
0
Спасибо)
Похожие вопросы
Предмет: Математика,
автор: maksudovrufat2a
Предмет: Право,
автор: katyakk0528
Предмет: Физика,
автор: mazhitovas200864
Предмет: Алгебра,
автор: misteroguzow
Предмет: Математика,
автор: kmocrecowa